Effects of cadmium on the behaviour of Cnesterodon decemmaculatus. (23rd July 2020) - Ferro, J.P.; Campos, L.B.; Ossana, N.A.; Ferrari, L.; Eissa, B.L.
Recognising biomarkers for assessing early ecotoxicity effects using test species exposed to reference toxicants is important, hence the aim of this work was to study changes in some behavioural parameters of Cnesterodon decemmaculatus. Fish were under stress conditions induced by exposure to a subtoxic concentration of cadmium (Cd) in the laboratory. Acute bioassays (96 h) were performed under laboratory conditions, with medium renewal every 48 h. Animals were randomly assigned into two groups of 10 individuals each: Cd-exposed (0.50 mg Cd. L -1 ) and control (moderate tap water). Both groups were video-recorded every day for 15 min at the same time of day. Each individual was evaluated for: a) aggressive behaviour; b) sexual behaviour; and c) swimming alterations. Fish exposed showed irregular swimming, hyperactivity periods, fewer copulation attempts and same aggressive behaviour as compared with the control group. Our results suggest that these behavioural alterations may serve as early and reliable biomarkers.